Quantitative determination of microorganisms in the intestines of rats - Bukina, Yu.; Букіна, Юлія Вячеславівна (My University, 2020)
The intestinal microbiome significantly affects the functioning of the body: it participates in metabolic processes, inhibition of pro-inflammatory reactions, in the formation of innate and adaptive immune response in the intestinal mucosa [1-4]. The most important function of the intestinal microbiome is to protect the body from pathogenic microorganisms - pathogens of bacterial intestinal infections [5, 6]. It is known that dysbiotic changes in the intestine lead to increased susceptibility to pathogenic bacteria, such as salmonella [7, 8], which are the etiological factor of gastroenteritis [9]. One of the most common causes of microbiota changes is the use of antibiotics [10-12]. Therefore, of particular interest are the processes of interaction of antibiotics, Salmonella enteritidis and Salmonella typhimurium with representatives of the normal intestinal microflora [13-15].